2017
DOI: 10.3389/fpls.2017.00396
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of microRNA319a and Its Putative Target Gene, PvPCF5, in the Bioenergy Grass Switchgrass (Panicum virgatum)

Abstract: Due to its high biomass yield, low environmental impact, and widespread adaptability to poor soils and harsh conditions, switchgrass (Panicum virgatum L.), a warm-region perennial herbaceous plant, has attracted much attention in recent years. However, little is known about microRNAs (miRNAs) and their functions in this bioenergy grass. Here, we identified and characterized a miRNA gene, Pvi-MIR319a, encoding microRNA319a in switchgrass. Transgenic rice lines generated by overexpressing the Pvi-MIR319a precurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…All TCP proteins contain a highly conserved TCP domain which is a 59-amino-acid non-canonical basic-helix-loop-helix (bHLH) motif at the N-terminus and functions in DNA binding, protein–protein interaction, and protein nuclear localization ( Kosugi and Ohashi, 2002 ; Aggarwal et al, 2010 ; Martin-Trillo and Cubas, 2010 ; Dhaka et al, 2017 ). So far, TCP genes have been identified in various plant species including Arabidopsis , rice, tomato, tobacco, and strawberry as shown in Supplementary Figure S1 ( Palatnik et al, 2003 ; Li et al, 2005 ; Aguilar-Martinez et al, 2007 ; Ori et al, 2007 ; Yao et al, 2007 ; Schommer et al, 2008 ; Nag et al, 2009 ; Giraud et al, 2010 ; Koyama et al, 2010b ; Sarvepalli and Nath, 2011 ; Yang et al, 2012 ; Ma et al, 2014 ; Parapunova et al, 2014 ; Wang et al, 2015b ; Chen et al, 2016 ; Lin et al, 2016 ; Ma et al, 2016 ; Wei et al, 2016 ; Zhou et al, 2016 ; Du et al, 2017 ; Xie et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…All TCP proteins contain a highly conserved TCP domain which is a 59-amino-acid non-canonical basic-helix-loop-helix (bHLH) motif at the N-terminus and functions in DNA binding, protein–protein interaction, and protein nuclear localization ( Kosugi and Ohashi, 2002 ; Aggarwal et al, 2010 ; Martin-Trillo and Cubas, 2010 ; Dhaka et al, 2017 ). So far, TCP genes have been identified in various plant species including Arabidopsis , rice, tomato, tobacco, and strawberry as shown in Supplementary Figure S1 ( Palatnik et al, 2003 ; Li et al, 2005 ; Aguilar-Martinez et al, 2007 ; Ori et al, 2007 ; Yao et al, 2007 ; Schommer et al, 2008 ; Nag et al, 2009 ; Giraud et al, 2010 ; Koyama et al, 2010b ; Sarvepalli and Nath, 2011 ; Yang et al, 2012 ; Ma et al, 2014 ; Parapunova et al, 2014 ; Wang et al, 2015b ; Chen et al, 2016 ; Lin et al, 2016 ; Ma et al, 2016 ; Wei et al, 2016 ; Zhou et al, 2016 ; Du et al, 2017 ; Xie et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, to verify the direct interaction between miR319 and OsTCP21 and OsGAmyb , respectively, we used a rapid transient assay in Nicotiana benthamiana which has been reported previously (Xie et al, 2017; Palatnik and Weigel, 2019). The results showed that the tobacco leaves generated GFP fluorescence injecting with 35S: OsTCP21 ‐GFP, 35S: OsGAmyb ‐GFP or empty vectors with GFP (35S:GFP) respectively, whereas co‐expression with 35S: MIR319a greatly reduced the GFP signal (Figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…To increase fermentable sugar or yield of biofuels, it requires to improve the relative amount of cell wall components, like cellulose or non-structural carbohydrates, reduced lignin content, and expression of endogenous hydrolyzing proteins that support more saccharification process [148,149]. Recently, large numbers of miRNAs and genes have been examined, which regulate cell wall synthesis, compositions, and bio-recalcitrance in a wide variety of plants [129,148,150]. It is well known that bio-recalcitrance is a major limiting factor that is mainly responsible for up to 45-55% total cost of biofuel production [108,151].…”
Section: The Role Of Mir156 In the Reduction Of Bio-recalcitrancementioning
confidence: 99%